A correlation study of music training, adult attachment, and personality traits using a large-sample questionnaire - Liu, Ying; Liu, Xiaolin; Zheng, Maoping (Frontiers in Psychology, 2023)
Music training can provide benefits to psychological health and is strongly associated with adult attachment style and personality traits through bidirectional interactions. A large sample including 10,191 Chinese musicians and non-musicians completed the Relationship Questionnaire and Big-Five Personality Inventory. Connections between music training, adult attachment, and personality were analyzed with the following results: (1) personality traits were correlated with attachment dimensions, with positive correlations between secure attachment and extroversion and between dismissing attachment and neuroticism; (2) music training was connected with the secure and fearful-avoidant attachment dimensions, which complemented the effect of educational level in the preoccupied and dismissing dimensions; (3) music training enhanced extroversion, openness, agreeableness, and conscientiousness, which interacted to affect extroversion and openness by gender; and (4) music training enhanced the regression of extroversion to preoccupied and secure attachments, and the regression of openness to preoccupied attachment. Conclusively, music training enhanced the connection between secure attachment and positive personality traits and regulated the correlation between insecure attachment and neuroticism. This analysis provides a large sample of statistical and practical evidence for the clinical practices of mental health and the educational and music training practices of co-cultivating cultural knowledge and artistic quality.